Back Cover: Teaching new tricks to old dogs: A review of drug repositioning of disulfiram for cancer nanomedicine (View 4/2021). Issue 4 (29th August 2021) - Zhao, Pengfei; Tang, Xueping; Huang, Yongzhuo
Abstract : Drug repurposing is an economical and efficient avenue to develop new therapeutics. Disulfiram is an anti‐alcoholism drug in clinical use for over sixty years, and its anti‐cancer activity has been actively explored in preclinical and clinical studies. In article number 20200127, Yongzhuo Huang and co‐wokers shows that nanomedicine provides a useful strategy for boosting the R&D of drug repositioning. Disulfiram‐based nanotherapy exhibits great promise in enhancing tumor‐targeted delivery efficiency and anticancer efficacy.